Effect of Rumex dentatus on Gastrointestinal Protection and Toxicology in Rodents via Investigating H+/K+-ATPase, Calcium Channels, and PDE Mediated Signaling - Qazi, Neelam Gul; Khan, Arif-ullah; Abbasi, Sumra Wajid; Malik, Imran; Naeem, Komal (Frontiers in Pharmacology, 2022)
This present study aimed to delineate Rumex dentatus crude extract (Rd.Cr), n-Hexane, ethyl acetate, aqueous fractions (Rd.n-Hex, Rd.ETAC, Rd.Aq) and emodin for antidiarrheal, antisecretory effects, isolated tissue preparation, gastrointestinal transient time, anti H. pylori, antiulcer effects and toxicology. Plant extracts attributed dose-dependent protection against castor oil-induced diarrhea and dose-dependently inhibited intestinal fluid secretions in mice. They decreased the distance moved by charcoal in the gastrointestinal transit model in rats. In rabbit jejunum preparations, it causes a concentration-dependent relaxation of both spontaneous and K+ (80 mM)-induced contraction, Rd.n-Hex and verapamil was relatively potent against K+-induced contractions and shifted the Ca2+ concentration–response curves (CRCs) to the right, Rd.Cr and Rd.ETAC shifted the isoprenaline-induced inhibitory CRCs to the left, showing potentiating effect similar to papaverine. Rd,n-Hex showed anti-H.pylori effect. Extracts and emodin also shows inhibitory effect against H+/K+-ATPase. Rumex dentatus showed gastroprotective and antioxidant effect. Histopathological evaluation showed improvement in cellular architecture and decrease in expression of inflammatory markers such as, cyclooxygenase (COX2), tumor necrosis factor (TNF-α) and phosphorylated nuclear factor kappa B (p-NFƙB), validated through immunohistochemistry, ELISA and western blot techniques. In RT-PCR it decreases H+/K+-ATPase mRNA levels. We also analysed certain safety aspects of Rumex dentatus and it exhibited a relative safety profile as no impairment was observed in kidneys, heart, liver and brain further assisted by biochemical and hematological analysis. Docking studies revealed that emodin against H+/K+-ATPase pump and voltage gated L-type calcium channel showed E-value of -7.9 and -7.4 Kcal/mol respectively. MD simulations MMPBSA/GBSA findings are consistent with the in-vitro, in-vivo and docking results. In conclusion, Rumex dentatus extracts and its phytoconstituent could be considered as a potent antioxidant and anti-inflammatory drug candidates that possess anti-diarrheal, anti-secretary, antispasmodic, anti H. pylori and anti-ulcer potential. It belongs to group 5 (LD50 > 2000 mg/kg), which suggests that it is in lower toxicity class.